1998
DOI: 10.1007/bf01450901
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of familial Mediterranean fever with sacroiliitis and Behçet's disease: A rare occurrence

Abstract: Familial Mediterranean fever (FMF) and Behçet's disease are relatively rare but may still coexist in the same patient. Sacroiliitis is another feature whose significance is controversial in either of the diseases. We report a case of longstanding FMF with sacroiliitis who later developed typical characteristics of Behçet's disease. Although occurrence by chance cannot be ruled out, this unusual patient may enhance the claims that FMF and Behçet's disease have common aetiopathogenetic mechanisms. It would be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…In spite of the distinct clinical features of BD and FMF, they share many common features, such as abnormal neutrophil activation and the effectiveness of colchicine. The MEFV gene mutation that is responsible for FMF has been reported to probably be a susceptibility factor for BD, and both disorders can occur concurrently in a single patient (10,18,24,25). The present patient did not have symptoms of BD other than recurrent fever and the ileal ulcers.…”
Section: Discussionmentioning
confidence: 47%
“…In spite of the distinct clinical features of BD and FMF, they share many common features, such as abnormal neutrophil activation and the effectiveness of colchicine. The MEFV gene mutation that is responsible for FMF has been reported to probably be a susceptibility factor for BD, and both disorders can occur concurrently in a single patient (10,18,24,25). The present patient did not have symptoms of BD other than recurrent fever and the ileal ulcers.…”
Section: Discussionmentioning
confidence: 47%
“…Given that, most of the FMF-associated vasculitis cases had MEFV gene mutations, contributing role of these mutations for vasculitis development may be considered in the pathogenesis. In line with this view, our literature search showed that most of the FMF patients reported in literature with coexistent HSV or PAN had [7,9,10,13,14,65,66] Medium vessel vasculitic diseases Polyarteritis nodosa [7, 8, 11-13, 15, 70, 71] Large vessel vasculitic diseases Unreported Unclassified vasculitic conditions Protracted febrile myalgia [16,60,[72][73][74] Behçet's disease [17,18,79] Cutaneous vasculitis [87,88] either homozygous or compound heterozygous M694V mutations. However, since many FMF patients carrying these mutations do not have associated vasculitis, we admit that this coexistence cannot solely be explained by the presence of MEFV gene mutations.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 57%
“…Then, the first case report of (BD) association with FMF appeared in literature in 1998 by Birlik et al [18]. However, the association of FMF and BD could not be shown in some other studies.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 95%
“…Another hypothesis is that the P706 polymorphism impairs the gene regulation through a change in the tridimensional conformation of the DNA molecule. One percent of FMF patients also suffer from inflammatory bowel disease, PAN or BD (Birlik et al, 1998;Cattan et al, 2000;Ozdogan et al, 1997;Ozen et al, 1999;Schwartz et al, 1997;Schwartz et al, 2000). Patients who had the clinical and genetic diagnosis of FMF can also develop vasculitis (Tekin et al, 1999;Tekin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%